The analysis of stray losses in tape wound concentrated windings of the permanent magnet synchronous motor. Issue 3 (5th May 2015) - Demenko, Ivo Doležel, Kay Hameyer, Wojciech Pietrowski; Krzysztof Zawirski, Andrzej; Wojciechowski, Rafal M.; Jedryczka, Cezary
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to analyse the stray losses in the windings of permanent magnet synchronous machines (PMSM). Design/methodology/approach – The 2D field model, based on the edge element method (EEM) and A -V formulation, has been developed and utilized for the determination and analysis of stray losses in the PMSM with concentrated windings made of strip conductors. The influence of the supply frequency as well as the slot opening width on the losses caused by eddy currents has been examined. The different arrangements of the conductors in the tape wound coils have been studied. The obtained results have been compared to the reference case when the eddy current effect is neglected. Findings – The usefulness of the proposed methodology of the stray losses evaluation has been tested on the case study problem. It has been observed that the stray losses in the windings of the considered machine can be reduced by choosing the proper value of the slot opening. The dependence of the stray losses on the frequency of the supply currents has been examined. The obtained results show that with the increase of frequency the stray losses caused by the eddy currents in the strip conductors increase. Originality/value – The proposed 2D field numerical model makes it possible to analyse the stray losses in the tape wound concentrated windings of the PMSM motor. The presented model can be utilized for the optimization of the magnetic circuit of the machine with the aim of minimizing eddy current losses.